2019
DOI: 10.1038/s41598-019-52490-1
|View full text |Cite
|
Sign up to set email alerts
|

A Study Comparing the Effects of Targeted Intra-Arterial and Systemic Chemotherapy in an Orthotopic Mouse Model of Pancreatic Cancer

Abstract: Systemic chemotherapy is the first line treatment for patients with unresectable pancreatic cancer, however, insufficient drug delivery to the pancreas is a major problem resulting in poor outcomes. We evaluated the therapeutic effects of targeted intra-arterial (IA) delivery of gemcitabine directly into the pancreas in an orthotopic mouse model of pancreatic cancer. Nude mice with orthotopic pancreatic tumors were randomly assigned into 3 groups receiving gemcitabine: systemic intravenous (IV) injection (low:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Tanaka et al [17] demonstrated that pancreatic arterial infusion chemotherapy produces higher regional drug concentrations in the pancreas. Rezaee et al's [14] study compared the effects of RAIC and SIC using an orthotopic mouse model of pancreatic cancer and found that RAIC significantly inhibited tumor growth. If the SIC regimen achieves the same results as RAIC, more than 300 times the dose of the drug must be used.…”
Section: Selection Of the Reported Results Overall Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…Tanaka et al [17] demonstrated that pancreatic arterial infusion chemotherapy produces higher regional drug concentrations in the pancreas. Rezaee et al's [14] study compared the effects of RAIC and SIC using an orthotopic mouse model of pancreatic cancer and found that RAIC significantly inhibited tumor growth. If the SIC regimen achieves the same results as RAIC, more than 300 times the dose of the drug must be used.…”
Section: Selection Of the Reported Results Overall Biasmentioning
confidence: 99%
“…[13] In some animal experiments and clinical trials, the therapeutic effect of RAIC has obvious advantages. [14][15][16][17] RAIC may be a new idea to improve the prognosis of pancreatic cancer. This study aims to evaluate the role of RAIC in the treatment of advanced pancreatic cancer by comparing the effectiveness and safety of RAIC and SIC.…”
Section: Introductionmentioning
confidence: 99%
“…New ideas are circulating in terms of how to target the delivery of chemotherapeutics innovatively and differently than what has been done before. One study suggests studying the combination of nanoparticle drug delivery systems with intra-arterial delivery systems [ 49 ]. Intra-arterial delivery has been studied separately from nano-targeted delivery but bringing the two together could provide an innovative answer for pancreatic cancer.…”
Section: Comparison Among Targeting Approachesmentioning
confidence: 99%
“…In a recent study using an orthotopic mouse model of pancreatic cancer, gemcitabine was delivered intra-arterially, and this suppressed tumor growth compared to dosing intravenously, which could result in poor patient outcomes due to significant toxicity. Intra-arterial delivery, however, can deliver a chemotherapeutic directly to the pancreas [ 49 ].…”
Section: Comparison Among Targeting Approachesmentioning
confidence: 99%
“…Hence, in the present work, we will examine the delivery of BM-MSCs into a mouse model using modification of techniques that we have previously developed to locally deliver therapies into the pancreas. 29 , 30 We will deliver BM-MSCs at the onset of diabetes which we will coordinate at the same time of STZ injection into C57BL/6 mice.…”
Section: Introductionmentioning
confidence: 99%